2021
DOI: 10.3390/app11177889
|View full text |Cite
|
Sign up to set email alerts
|

Natural Dietary and Medicinal Plants with Anti-Obesity Therapeutics Activities for Treatment and Prevention of Obesity during Lock Down and in Post-COVID-19 Era

Abstract: Overweight and obesity have become global epidemics, especially during the lockdown due to the COVID-19 pandemic. The potential of medicinal plants as a better and safe option in treating obesity and overweight has gained attention in recent years. Obesity and overweight has become a major public health concern, and its incidence rising at an alarming rate. Obesity is one of the major types of metabolic syndrome, resulting in various types of problems such as hypertension, diabetes, dyslipidemia, and excess fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 244 publications
(168 reference statements)
0
10
0
Order By: Relevance
“…Phenolic compounds are known for their notable potential activity against various human viruses, and phenolic compounds also have immunomodulatory and anti-inflammatory activity [ 27 ]. The most abundant phenolic compounds are phenolic monoterpenes (carvacrol and thymol) and diterpenes (carnosol, carnosic acid, and methyl carnosate), hydroxybenzoic acids ( p -hydroxybenzoic, protocatechuic, gallic, vanillic, catechol, and ellagic), phenylpropanoic acids ( p -coumaric, caffeic, rosmarinic, chlorogenic, ferulic, cryptochlorogenic, and neochlorogenic), phenylpropenes (eugenol), coumarins (herniarin and coumarin), flavanoes (naringenin, eriocitrin, naringin, and hesperidin), flavones (apigenin, apigetrin, genkwanin, luteolin, luteolin 7-glucuronide, cynaroside, scolymoside, salvigenin, and cirsimaritin), and flavanols (catechin, astragalin, kaempferol, methyl ethers, quercetin, hyperoside, isoquercetin, miquelianin, and rutin) [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds are known for their notable potential activity against various human viruses, and phenolic compounds also have immunomodulatory and anti-inflammatory activity [ 27 ]. The most abundant phenolic compounds are phenolic monoterpenes (carvacrol and thymol) and diterpenes (carnosol, carnosic acid, and methyl carnosate), hydroxybenzoic acids ( p -hydroxybenzoic, protocatechuic, gallic, vanillic, catechol, and ellagic), phenylpropanoic acids ( p -coumaric, caffeic, rosmarinic, chlorogenic, ferulic, cryptochlorogenic, and neochlorogenic), phenylpropenes (eugenol), coumarins (herniarin and coumarin), flavanoes (naringenin, eriocitrin, naringin, and hesperidin), flavones (apigenin, apigetrin, genkwanin, luteolin, luteolin 7-glucuronide, cynaroside, scolymoside, salvigenin, and cirsimaritin), and flavanols (catechin, astragalin, kaempferol, methyl ethers, quercetin, hyperoside, isoquercetin, miquelianin, and rutin) [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obesity are among the most challenging global health problems, with economic and social costs increasing at alarming rates worldwide (El-Shiekh et al, 2019;Karri et al, 2019;Sun et al, 2021;World Obesity, 2022). It is a multifactorial problem resulting from the excessive energy storage in the form of lipids in the adipocytes, which can lead to numerous life-threatening diseases associated with abnormal body fat accumulation, including type 2 diabetes, dyslipidemia, cardiovascular diseases, osteoarthritis, psychiatric pathologies such as depression, anxiety and mental disorders, obstructive sleep apnea, and certain types of cancer (Bautista et al, 2019;El-Shiekh et al, 2019;Islam et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is a multifactorial problem resulting from the excessive energy storage in the form of lipids in the adipocytes, which can lead to numerous life-threatening diseases associated with abnormal body fat accumulation, including type 2 diabetes, dyslipidemia, cardiovascular diseases, osteoarthritis, psychiatric pathologies such as depression, anxiety and mental disorders, obstructive sleep apnea, and certain types of cancer (Bautista et al, 2019;El-Shiekh et al, 2019;Islam et al, 2020). These nutritional pathologies enormously impact people's mortality, morbidity, and quality of life (Sun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is generally attributed to unhealthy eating, and a healthy plant-based diet may thus be beneficial in lowering inflammatory markers [5][6]. Besides, several studies have shown that many plants effectively prevent obesity [7], e.g., onion, Aloe vera, cumin, garcinia gummi-gutta, roselle, yerba mate, Asian lobelia, mango, and black pepper [8]. Natural products can act as anti-obesity agents through different mechanisms, including augmentation of energy expenditure, appetite suppression, and inhibitions of lipase enzyme, adipocyte differentiation, and lipid metabolism [9].…”
Section: Introductionmentioning
confidence: 99%